Histórias em quadrinhos na biblioteca - Amarante, Raylson Souza (Brasil, 2022)
Given that the content of comics is criticized as unimportant material, the research is about comic books in the library, with intention to clarify about how comics can be used as a source of information and add some value to the reader. Knowing that, the research’s goal is about the impact and incision in the stories in comic books in the social culture and its applicability in the library. It’s made a research in comparative method of an applied nature and with a qualitative approach is carried out, furthermore, it was used the bibliographic research to intent to do a survey of information on the subject. The scientific analysis occurred with the Google Academic utilization. With this information, is possible to note the results achieved show the real importance of the stories in the comic books in the library, inasmuch as, it can be used to assistance as source of information and contribute in reading formation.